The relationship of quality perfomance appraisal experience on job satisfaction and organizational commitment / Syarifah Hakimah Syed Affendy - Syed Affendy, Syarifah Hakimah (Faculty of Business and Management, 2013)
Nowadays, the performance appraisal is the important thing to all organization, especially when the organization recognized the benefit and function of perfonnance appraisal in order to increase employee perfonnance. Therefore, the purpose of this study is to examine the relationship between quality performance appraisal experience on job satisfactions and organizational commitment at the Melaka Hari Ini (MHI) Sdn Bhd, Ayer Keroh, Malacca. In order to identify the relationship between quality performance appraisal experience with job satisfaction and organizational commitment, 40 sets of questionnaire has been distributed to the Melaka Hari Ini (MHI) Sdn Bhd. Based on the research objectives and research questions that had been developed, the findings showed that the employee's job satisfaction and organizational commitment had been increased when the organization adapt the performance appraisal into the working environment. Furthermore, based on the findings of correlation it was fOlmd that the job satisfaction and organization commitment have a positive relationship with performance appraisal. Moreover, the organization can provide better of performance appraisal in the organization which can help the employees to increase the job satisfaction and more committed in the organization.